STUDY OF SPECTROSCOPY REFLECTANCE TO EXPLORING REE-BEARING MINERALS ASSOCIATED USING REMOTE SENSING IN SOUTH BANGKA REGION, BANGKA-BELITUNG PROVINCE - Anugrah Firdaus, Muhammad
As one of the region traversed by the Southeast Asian tin belt, tin potential in Indonesia has a large amount. The potential are distributed well in the main tin producing areas, one of which is Bangka Island. The presence of tin is associated with several rare earth element (REE) bearing minerals such as monazite, xenotime and zircon. Considering that REE has many benefits, it is necessary to conduct research and mapping to determine the abundance of REE so that it can provide an overview the potential of REE in Indonesia especially in the South Bangka region. Mapping can be done by studying the spectral characteristics of the REE bearing minerals as a database for use in mapping using remote sensing. This research aims to study the spectral characteristics of REE-bearing minerals and identify their presence and mapping the distribution of these minerals using Sentinel-2 optical imagery and Sentinel-1 SAR imagery. The mapping method used is the band ratio, band peak, band depth and band math. In addition, several laboratory analyzes of field samples have been carried out, such as X-ray diffraction, scanning electron microscopy/energy dispersive X?ray spectrometry and inductively coupled plasma-mass-spectrometry analysis. Wavelengths that are key to the presence of major REE-bearing minerals, especially at visible – near infrared wavelengths and several in shortwave infrared The abundance of REE is indicated by the high TREE found in the tailings and aluvial sample at a size fraction of +150#. Band 8a on Sentinel-2 can be the key in detecting the presence of REE because it is related to the Nd absorption feature. Areas with high indications of REE concentrations are distributed in open areas without vegetation, which are abandoned tin mine sites. With the results of this study, it is expected that the existence and abundance of REE in Indonesia, especially in the South Bangka region, can be known.